Pou4f1-Tbr1 transcriptional cascade controls the formation of Jam2-expressing retinal ganglion cells - Kiyama, Takae; Altay, Halit Y.; Badea, Tudor C.; Mao, Chai-An (Frontiers in Ophthalmology, 2023)
More than 40 retinal ganglion cell (RGC) subtypes have been categorized in mouse based on their morphologies, functions, and molecular features. Among these diverse subtypes, orientation-selective Jam2-expressing RGCs (J-RGCs) has two unique morphologic characteristics: the ventral-facing dendritic arbor and the OFF-sublaminae stratified terminal dendrites in the inner plexiform layer. Previously, we have discovered that T-box transcription factor T-brain 1 (Tbr1) is expressed in J-RGCs. We further found that Tbr1 is essential for the expression of Jam2, and Tbr1 regulates the formation and the dendritic morphogenesis of J-RGCs. However, Tbr1 begins to express in terminally differentiated RGCs around perinatal stage, suggesting that it is unlikely involved in the initial fate determination for J-RGC and other upstream transcription factors must control Tbr1 expression and J-RGC formation. Using the Cleavage Under Targets and Tagmentation technique, we discovered that Pou4f1 binds to Tbr1 on the evolutionary conserved exon 6 and an intergenic region downstream of the 3’UTR, and on a region flanking the promoter and the first exon of Jam2. We showed that Pou4f1 is required for the expression of Tbr1 and Jam2, indicating Pou4f1 as a direct upstream regulator of Tbr1 and Jam2. Most interestingly, the Pou4f1-bound element in exon 6 of Tbr1 possesses high-level enhancer activity, capable of directing reporter gene expression in J-RGCs. Together, these data revealed a Pou4f1-Tbr1-Jam2 genetic hierarchy as a critical pathway in the formation of J-RGC subtype.